Pelatihan Pembuatan Pestisida Berbahan Aktif Sulfur Sebagai Bahan Serbaguna Penyelesaian Permasalahan Petani Desa Slateng, Ledokombo, Jember - Basuki, Basuki; Farisi, Oria Alit; Sari, Vega Kartika; Mandala, Marga; Ristiyana, Suci; Utami, Ratih Apri; Destiawan, Hisyam Azhar; Safitri, Urmita Dwi; Susanto, Devani Avrillia; Isnanto, Bimo Arvi Aji; Kesumowati, Dyah Ayu (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
The majority of the people of Slateng Village, Ledokombo, and Jember are farmers whose main commodities are food and horticultural crops, which have high potential. However, there are crucial problems that threaten to reduce food crop productivity. This problem arises as a result of the large number of pests that attack. Pest management outreach and training in making natural pesticides made from the active ingredient sulfur or jadam sulfur, understanding the problems, and solving existing problems. Community service activities are carried out in several stages. First, socialization and counseling are carried out regarding the types of agricultural pests. Second, the socialization of the use of jadam sulfur pesticide as a multi-purpose pest treatment. Third, an explanation of the composition of sulfur jadam based on monitoring results. Lastly, training in making sulfur jadam. Through this outreach and training, farmers' knowledge of managing agricultural pests increases.